The use of verbal images (lexical-syntactic) in SheykhSharzīn’s Scroll - Zohreh Fadaie Veshki; Mah Nazari (مطالعات زبانی و بلاغی)
Language is an intertwined network of layers, links, and visual signs. Sheykh Sharzīn’s Scroll is one of the magnificent works of contemporary artistic prose, which has been compiled in the form of a screenplay with linguistic images and literary style. The creator of this work is Bahrām Beyzāī, an Iranian author with well-thought-out ideas, who has beautifully and artistically represented his thought in a multi-layered language of rhythmic Beyhaqī-like prose and  verbal and visual images in this screenplay. This article examines the use of verbal images at lexical and syntactic levels. Factors such as profuse diction, proportion, blend of old and new languages, old syntactic structure and irregular syntactic arrangement have given a special prominence to Beyzāī’s text. The use of lexical, temporal, and stylistic meta-norms and beautiful dramatic staging have played an important role in spiritual fulfillment, inducement of cultural, social and historical themes and the formation of the literary style of the screenplay. The aim of this article is to show how the use of lexical and syntactic images have been effective in creating the poetic prose, artistic descriptions and dramatic effects of this screenplay. The research method is descriptive-analytical, text-based and with regard to literary stylistics. Research findings indicate the effect of the use of verbal and dramatic images in the prominence of the screenplay of Sheykh Sharzīn’s Scroll in the fields of culture, language, literature and dramatic literature.